1991
DOI: 10.1099/00207713-41-3-358
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of New Methanothrix Strains

Abstract: Mesophilic Methanothrix sp. strains MTAS and MTKO were isolated as pure cultures from the sludge of anaerobic digestors. We examined the relationships between these two isolates and three other Methanothrix strains (strains Opfikon' [T = type strain], GP(il', and FE) by using an immunological method, by performing DNA homology experiments, and by analyzing polar lipids. Our results indicate that all five strains belong to the same species.Acetate is the precursor of at least 60% of the methane produced during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Until the mid-seventies of this century, therefore, it was doubted that an organism could grow anaerobically on acetate [102]. Although up to now several organisms have been isolated which use acetate as sole energy source under anaerobic conditions, the problem of energy conservation in this process is not yet solved [26][27][28][29][30][31][32][33][34].…”
Section: Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until the mid-seventies of this century, therefore, it was doubted that an organism could grow anaerobically on acetate [102]. Although up to now several organisms have been isolated which use acetate as sole energy source under anaerobic conditions, the problem of energy conservation in this process is not yet solved [26][27][28][29][30][31][32][33][34].…”
Section: Energeticsmentioning
confidence: 99%
“…The bacterium was renamed Methanothrix soehngenii, with the Op- fikon strain as type strain [26][27][28]. Thereafter, several Methanothrix strains have been described, including the mesophilic Methanothrbc soehngenii strain FE, MTAS and MTKO and Methanothrix concilli GP-6 v nd the thermophilic strains Methanothrix CALS-1, PT and Methanothrlx thermoacetc~'~dla [29][30][31][32][33][34]. Although immunological studies with antisera showed only a weak relationship between the different Methanothrix species, Touzel unified the strains Opfikon, FE and GP-6 into one species, Methanothrix soehngenii, on the basis DNA-DNA hybridization studies [29,35].…”
Section: Introductionmentioning
confidence: 99%
“…After this description, several mesophilic Methanothrix strains were isolated or "highly purified" (8,10,18,20,26). A thermophilic Methanothrix strain was first enriched from thermal lake mud by Nozhevnikova and Chudina (17), and these authors named their enriched organism (strain 2-517) Methanothrix thermoacetophila.…”
mentioning
confidence: 99%
“…Strain GP6 (OCM69) was from the Oregon Collection of Methanogens, Beaverton. Strains MTAS and MTKO were from our collection (9). Strain MTHI was isolated from an anaerobic sewage treatment plant in Hiagari, Kitakyushu, Japan.…”
mentioning
confidence: 99%
“…Strain MTHI was isolated from an anaerobic sewage treatment plant in Hiagari, Kitakyushu, Japan. All strains were cultivated at 37°C in 1-liter serum vials that contained 500 ml of bicarbonate-free medium, the pH of which was controlled at 7.0 with 50 mM MES [2-(N-morpholino)ethanesulfonic acid] buffer (9). For cultivation of strain GP6, the medium was supplemented with 2 g of yeast extract per liter.…”
mentioning
confidence: 99%